IMovie 3 solutions : - Sadun, Erica (Sybex, 2002)
iMovie 3 is the latest version of Apple's powerful yet accessible digital video editing software. Announced at Macworld Expo 2003, iMovie3 boasts a completely rewritten interface, seamless integration with other iLife products, and new pro-quality visual and audio effects